The specific leaf area of forest species subjected to different degrees of shading did not differ when detached and full leaflets were compared - Guimarães, Jacqueline Lucia; Hüther, Cristina Moll; Almeida, Ramonn Diego Barros de; Nogueira, Lilian Thurler; Carvalho, Luiza Ferreira de; Borella, Junior; Machado, Thelma de Barros; Pereira, Carlos Rodrigues (Semina: Ciências Agrárias, 2020)
Studies of forest species under different environmental conditions are essential for enhancing our understanding of plant-environment relationships. Different light conditions interfere with the production of seedlings within forests, and this interference can be verified by assessing leaf area. However, several species have leaf compound that often contain numerous leaflets, which makes the direct measurement of leaf area difficult. This leads researchers to question whether these types of leaves should be separated for analysis or measured whole. Thus, the aim of this study was to analyse specific leaf area in whole leaves and detached leaflets of six forest species subjected to different levels of shading. The forest species assessed all produced compound leaves and included Schinus terebinthifolius Raddi (aroeira), Schinopsis brasiliensis Engl. (braúna), Dalbergia nigra (Vell.) Fr. All. ex Benth. (jacaranda-da-bahia), Chorisia speciosa A. St.-Hil (paineira), Caesalpinia peltophoroides Benth (sibipiruna) and Plathymenia reticulata Benth (vinhático). Each species was subjected to six different degrees of shading: 0% (full sun); 20; 40; 60; 80 and 90%. Sombrite netting was used to shade plants. The analysis of the specific leaf area was performed using two different methods, which included the analysis of separate leaflets and whole leaves. To analyse leaflet area,50 leaflets per plant were assessed three times, and six plants per treatment were assessed. To assess whole leaves, data were obtained from the whole leaves of six plants per treatment. This process was repeated for all aforementioned species. Data obtained from both analysis methods indicated that all species assessed were similarly affected by shade, and leaf area varied according to the level of shading. This similarity of data demonstrates that, for these species, it is not necessary to use complex methods to obtain specific leaf area measurements. Thus, determining specific leaf by measuring the entire leaf provides results that did not statistically differ from those obtained by measuring individual leaflets.